2009
DOI: 10.1158/0008-5472.can-08-4007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Retinal Cadherin Facilitates Mammary Tumor Progression and Metastasis

Abstract: The mammary epithelium is thought to be stabilized by cell-cell adhesion mediated mainly by E-cadherin (E-cad). Here, we show that another cadherin, retinal cadherin (R-cad), is critical for maintenance of the epithelial phenotype. R-cad is expressed in nontransformed mammary epithelium but absent from tumorigenic cell lines. In vivo, R-cad was prominently expressed in the epithelium of both ducts and lobules. In human breast cancer, R-cad was down-regulated with tumor progression, with high expression in duct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…To further validate that the effects of N-cadherin on Akt3 expression were not because of confounding effects from other cadherins present in mammary epithelial cells such as R-cadherin, 16 we transfected N-cad-Myc into mouse L cells that are fibroblasts devoid of endogenous cadherins. In these cells, N-cad was also found to downregulate Akt3 expression without affecting Akt1 or Akt2 levels compared with control vector-transfected L cells (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…To further validate that the effects of N-cadherin on Akt3 expression were not because of confounding effects from other cadherins present in mammary epithelial cells such as R-cadherin, 16 we transfected N-cad-Myc into mouse L cells that are fibroblasts devoid of endogenous cadherins. In these cells, N-cad was also found to downregulate Akt3 expression without affecting Akt1 or Akt2 levels compared with control vector-transfected L cells (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of cadherins in MTC is poorly documented (28) and sunitinib treatment induced up-and downregulation of CDH4 or R-cadherin and CDH6, respectively. R-cadherin acts as a critical regulator of the normal phenotype and its loss contributes to epithelial suppression and metastatic progression (34). Aberrant expression of cadherin-6 is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, R-cadherin was high-level expression in ductal carcinoma in situ and reduced expression in invasive duct carcinomas. R-cad suppressed tumor formation and lung colonization in vivo and was associated with repression of the MMP1, MMP2, cyclooxygenase 2 (Cox2) gene signature characteristic of pulmonary metastasis [42]. Johnson et al showed that inappropriate expression of R-cadherin in BT-20 breast tumor cells results in decreased expression of endogenous caherins including E-, P-cdherin (cadherin switch), and induced cell motility via Rho GTPase activation [43].…”
Section: R-cadherinmentioning
confidence: 99%